P-288 Classical Epithelial NF-κB Activation Is Detrimental During Bacterial Infectious Colitis. (February 2017) - Mackos, Amy; Kim, Eunsoo; Boyaka, Prosper; Bailey, Michael
Abstract : Background: The inflammatory bowel diseases are multifactorial diseases in which genetic predispositions and a series of environmental changes contribute to the development and progression of intestinal inflammation contributed by inflammatory immune cells, including monocytes and neutrophils. While monocytes and neutrophils are necessary for tissue homeostasis and clearance of pathogens, an increased accumulation of inflammatory monocytes and neutrophils can lead to excessive inflammation and tissue damage. As a result, immune recruitment to the colon is tightly regulated. Mice challenged with the enteric pathogen Citrobacter rodentium (CR) develop a TH 1-mediated colitis that is attributed to monocyte-driven inflammation. Previous evidence demonstrates that CR-mediated monocyte recruitment is due to enhanced colonic CCL2 expression via classical NF-κB activation, however the cellular source of CCL2 has not been identified. Due to the intimate contact of CR with the colonic epithelial cell (CEC), we hypothesize that NF-κB-derived, CEC gene expression is necessary for the exacerbation of infectious colitis. Methods: In addition to C57BL/6 wild type (WT) mice, mice in which classical NF-κB activation is defective, via the deletion of IKKβ in intestinal epithelial cells (IKKβ ΔIEC ), were orally challenged with CR. Tissue was harvested on days 0, 3, and 12 post-challenge for histology, gene expression, and bacterial colonization analysis. Results: Prior to pathogen challenge, there was a significant increase in anti-inflammatory interleukin (IL)-10, tumor necrosis factor (TNF)-α, and inducible nitric oxide synthase (iNOS) in IKKβ ΔIEC mice as compared to non-infected WT counterparts. This may be due to an increase in basal activation of the alternative NF-κB pathway as evidenced by enhanced colonic p52 activation in naïve IKKβ ΔIEC mice. Increased basal activity of colonic p52 may be protective as there was a significant reduction of colonic pathogen colonization in IKKβ ΔIEC mice as compared to WT mice throughout the 12 day pathogen challenge. There was also a significant reduction in colonic histopathology, colonic inflammatory mediator gene expression (i.e., TNF-α, iNOS, chemokines CCL2 and CXCL1), and colonic neutrophil accumulation in IKKβ ΔIEC mice as compared to day-matched WT mice. Additionally, there was a significant reduction of CD11b + monocytes and CD4 + T cells in infected IKKβ ΔIEC mesenteric lymph nodes when compared to infected WT mice. Conclusions: Although it is not yet known why IKKβ-deficient mice are more resistant to CR-induced pathology, we believe that classical epithelial activation of NF-κB exacerbates CR-induced infectious colitis while alternative NF-κB activation, via p52, prior to pathogen challenge creates an unfavorable environment for CR colonization. However, upon colonization there is a reduction in inflammatory mediator gene expression in IKKβ-deficient mice, including a reduction of colonic CCL2 and CXCL1, monocyte and neutrophil chemoattractant genes, respectively. Thus, we conclude that colonic classical epithelial NF-κB activation is detrimental during infectious colitis.